Predictive value of geriatric nutritional risk index in patients with pancreatic cancer: a meta-analysis - Hua, Yaqi; Yuan, Yi; Zhou, Chen; Liu, Liping; Hu, Yan; Tu, Ping; Li, Dongying (Frontiers in Nutrition, 2025)
ObjectiveWhile growing evidence supports the Geriatric Nutritional Risk Index (GNRI) as a prognostic indicator for various cancers, its predictive value in pancreatic cancer remains unclear. This meta-analysis systematically evaluates GNRI’s ability to predict postoperative complications and long-term outcomes in pancreatic cancer patients.MethodsWe conducted a comprehensive literature search across nine databases (Web of Science, PubMed, Embase, Cochrane Library, Scopus, WanFang, CNKI, VIP, and SinoMed) through June 1, 2025. Hazard ratios (HRs) with 95% confidence intervals (CIs) were used to assess overall survival (OS), while risk ratios (RRs) with 95% CIs evaluated postoperative complications.ResultsFrom 233 initially identified studies, 10 met inclusion criteria (n = 2,003 patients). Pooled analysis revealed that lower GNRI significantly predicted worse OS (HR = 1.92, 95% CI 1.54–2.41, p < 0.0001) and higher postoperative pancreatic fistula (POPF) incidence (RR = 0.18, 95% CI 0.08–0.43, p < 0.001). No significant association was found between GNRI and post-pancreatectomy hemorrhage (PPH) (RR = 0.21, 95% CI 0.03–1.53, p = 0.13).ConclusionGNRI shows promise as a clinically useful predictor of OS and POPF in pancreatic cancer patients. However, these findings require validation through prospective multicenter studies.Systematic review registrationIdentifier CRD42023409362.